Analisis Cluster Untuk Pengelompokkan Prestasi Mahasiswa Angkatan 2013 Fakultas MIPA Universitas Islam Madura - Zaifullah, Zaifullah; Yulianto, Tony (Universitas Islam Madura, 2022)
Student achievement is a person's mastery of certain knowledge or skills in a course, which is obtained from test scores or numbers given by the lecturer. Many factors affect student achievement, including parents' income, pocket money, distance to campus, length of time studying, student side jobs, and the existence of learning aids. Therefore, a research will be conducted using cluster analysis for grouping student achievement in the hope of mapping students so that it is easier for lecturers to teach students. In this case, four cluster analysis methods are used, namely single linkage, complete linkage, average linkage and k-means. Where the best grouping is obtained with the icdrate, namely average linkage. The results of the average linkage method obtained that the two groups were the lowest of the other five groups who had to get more guidance from other groups.